Effect of alkali-activated metakaolin cement on compressive strength of mortars - Kornnika Wianglor (2018)
© 2017 Elsevier B.V. This paper reports the compressive strength and microstructure characteristic of alkali-activated metakaolin (MK) cement under two curing methods. MK was used to replace part of Portland cement (PC) at 70, 80, 85, 90, 95 and 100% by mass of binder. Sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) were used as activating agents (Na2SiO3to NaOH ratio of 0.67). NaOH with 10 molar concentrations, liquid alkali/binder ratio of 0.8 and water base was used. Mortar and paste specimens were cured at 23 ± 2°C (55% RH) and 60°C (95% RH). The results indicated that calcium silicate hydrate (C–S–H) and calcium carbonate (CaCO3) phases were detected by thermogravimetry (TGA). Setting time and drying shrinkage decreased when metakaolin replacement level increased, the compressive strength of alkali-activated metakaolin cement increased with the increase of PC content and increased with temperature. The curing of specimens at 60°C (95% RH) enhanced the compressive strength, matrices appeared denser than when cured at 23 ± 2°C (55% RH) and phases of (C, N)-A-S-H gel and or C–S–H gel can be seen clearly.